2011
DOI: 10.1039/c0cc05176d
|View full text |Cite
|
Sign up to set email alerts
|

A Li–O2/CO2 battery

Abstract: A new gas-utilizing battery using mixed gas of O(2) and CO(2) was developed and proved its very high discharge capacity. The capacity reached three times as much as that of a non-aqueous Li-air (O(2)) battery. The unique point of the battery is expected to be the rapid consumption of superoxide anion radical by CO(2) as well as the slow filling property of the Li(2)CO(3) in the cathode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
256
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(281 citation statements)
references
References 11 publications
5
256
1
8
Order By: Relevance
“…Based on the reported results and the observations above, we propose the following preliminary view of the reaction mechanisms for the Na-O 2 /CO 2 cell. Mechanism 1 [10,13]: [14]. Since Na 2 C 2 O 4 is a discharge product, the following reactions are also possible:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the reported results and the observations above, we propose the following preliminary view of the reaction mechanisms for the Na-O 2 /CO 2 cell. Mechanism 1 [10,13]: [14]. Since Na 2 C 2 O 4 is a discharge product, the following reactions are also possible:…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the Li-O 2 /CO 2 battery [10], which specifically aims to use CO 2 to enhance the energy density of the Li-O 2 cell, the current work focuses on metal-CO 2 /O 2 batteries as platforms for CO 2 capture in a technology that also produces electrical energy. Both of these goals are met using a "primary" battery, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CO 2 and moisture in the ambient air can signifi cantly infl uence the electrochemical performance of a lithium/air cell with a negative impact over cyclability, even in small amounts. [36][37][38] For instance, lithium metal can react with H 2 O traces in the air and generate LiOH and H 2 . Aurbach and co-workers [ 36,37 ] reported that CO 2 also reacts with the Li + ions forming Li 2 CO 3 on the electrode surface, while Takechi et al [ 38 ] demonstrated that Li 2 CO 3 can form from the reaction between CO 2 and Li 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…An emerging branch of rechargeable batteries is based on the metal-air chemistry, featuring extremely high specific energy (W h kg À1 )/energy density (W h L À1 ) and inexhaustible and storage-free cathode reactants. [1][2][3][4][5][6][7][8][9][10][11] However, key issues limiting the commercial development of the conventional metal-air batteries (e.g., lithium-air, iron-air and zinc-air) for mid-scale transportation and large-scale stationary applications are the poor reversibility and low rate capacity arising from technical issues such as congestion of airpathways by the formation of condensed oxides, 6 precipitation of carbonates in electro-catalyst's pores in the air-electrode, 7,8 and evaporation/decomposition of liquid organic solvent electrolytes. 7,[9][10][11] Recently, we demonstrated a novel concept of the ''all solid-state metal-air battery'' that innovatively combines a regenerative solid oxide fuel cell (or RSOFC) and a chemical-looping redox cycle unit (RCU).…”
mentioning
confidence: 99%